Demographic Factors Affecting University-Level Student’s Online Shopping Behavior in Pokhara Valley - Adhikari, Sujita; Ranabhat, Deepesh; Sapkota, Pradeep; Malla, Subash; Ranabhat, Mala (Janaprakash Journal of Multidisciplinary Research, 2024)
Today people are doing business online which has made human life much easier. Online shopping is becoming an integral part of the economy and country and worldwide increasingly. The purpose of this study is to find out demographic factors affecting university-level students’ online shopping behavior in Pokhara Valley. The study utilized quantitative research design, collecting data from 388 valid samples through a structured questionnaire. The data analysis involved descriptive and inferential analysis, including frequency analysis, mean difference test and chi-square test. Regarding online shopping behavior, a significant portion of respondents engage in online purchasing, primarily infl uenced by advertisements. However, online shoppers face problems such as poor product quality, product description discrepancies, and slow delivery services. Furthermore, education status emerged as significant determinants, while gender, marital status, ethnicity, family income and faculty showed no significant associations. The findings underscore the importance of addressing consumer concerns and tailoring strategies to diverse segments to enhance the online shopping experience.